2004
DOI: 10.2144/04365st01
|View full text |Cite
|
Sign up to set email alerts
|

Three new Drosophila markers of intracellular membranes

Abstract: The need for cellular markers that permit a quick and accurate evaluation of a protein's subcellular localization has increased with the surge of new data generated by the Drosophila genome project. In this report, we present three ubiquitously expressed Drosophila transgenes that expressed a green fluorescent protein variant (enhanced yellow fluorescent protein) that has been targeted to different intracellular membrane targets: the Golgi apparatus, mitochondria, and endoplasmic reticulum. These markers serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 10 publications
(5 reference statements)
3
68
0
Order By: Relevance
“…3). Simultaneous immunohistological stainings of Drosophila tissue with anti-Garz antibodies and for Golgi-EYFP (LaJeunesse et al, 2004) revealed that Garz is highly enriched in the ultra-proximal region of the Golgi complex, which corresponds to the cis-Golgi compartment ( Fig. 3A-I).…”
Section: Ems667mentioning
confidence: 99%
“…3). Simultaneous immunohistological stainings of Drosophila tissue with anti-Garz antibodies and for Golgi-EYFP (LaJeunesse et al, 2004) revealed that Garz is highly enriched in the ultra-proximal region of the Golgi complex, which corresponds to the cis-Golgi compartment ( Fig. 3A-I).…”
Section: Ems667mentioning
confidence: 99%
“…Instead, the Drosophila Golgi exists as distributed puncta, forming multiple organelles within a single cell (Kondylis and Rabouille, 2009; Stanley et al, 1997). As the major change in sff N-glycan expression is a shift towards greater complexity, we focused first on late Golgi compartments using markers described previously to delineate the medial/trans and trans-Golgi in Drosophila (LaJeunesse et al, 2004;Yano et al, 2005). We assessed the relative distributions of Golgi-YFP (a medial/trans marker, YFP fused to the transmembrane localization domain of human 4GalT), Arachis hypogaea lectin (PNA) binding (a trans marker, Gal3GalNAc specific lectin) and a neuronal protein (Fasciclin 2, Fas2) that bears an HRP epitope (Desai et al, 1994;Lin et al, 1994).…”
Section: Sff Modulates Golgi Compartmentation In Neuronsmentioning
confidence: 99%
“…4, 5). Transgenic flies targeting expression of an enhanced green fluorescent protein (GFP) variant to either the ER or trans-Golgi (LaJeunesse et al, 2004) were analyzed by immunostaining with anti-GFP (see the Experimental Procedures section). We also used an anti-KDEL antibody to label the ER or an anti-KDEL receptor (anti-KDEL-R) antibody to visualize the ER-Golgi intermediate compartment and cis-Golgi (Tang et al, 1993;Griffiths et al, 1994).…”
Section: Loj Localizes To Punctate Structures In the Cytoplasm Of Devmentioning
confidence: 99%
“…Purified IgG made against GST-Loj was used at a concentration of 7 g/ml with ovaries dissected from CS, EYFP-ER (LaJeunesse et al, 2004), EYFP-Golgi (LaJeunesse et al, 2004), or loj 00898 (Carney and Taylor, 2003) flies. EYFP-ER and EYFP-Golgi tissues were also incubated with a 1:50 dilution of mouse monoclonal antibody 3E6 anti-GFP (Molecular Probes).…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%